Розробка метрологічного забезпечення калібрувань засобів вимірювання геометричних розмірів - Пахомова, А. О.; Фоменко, В. Д. (ХНУРЕ, 2019)
The system of accounting and documenting the results of the verification of the suitability of measuring instruments for operation is proposed. A local validation scheme has been developed. The method of carrying out calibration of measuring instruments of geometric quantities, which provide the correct and unified procedure of calibration, is developed. Methods of comparative analysis of existing verification methods, national and international normative base in the field of metrological support of measuring instruments of geometric quantities, methods of statistical processing of measurement results are used.